The Molecular Mechanisms of Thalidomide Teratogenicity and Implications for Modern Medicine - Knobloch, J.; Jungck, D.; Koch, A. (Current Molecular Medicine, 2017)
Thalidomide is a teratogen that affects many organs but primarily induces limb truncations like phocomelia. Rodents are thalidomide resistant. In the 1950s, this has led to misinterpretations of animal tests and to the fatal assumption that the drug was safe for pregnant women to use against morning sickness. The result was one of the biggest scandals in medical history: 10.000 and more infants with birth defects in Europe. Nonetheless, thalidomide still has its place in modern medicine as it has strong therapeutic potential: it has been approved by the FDA for multiple myeloma and erythema nodosum leprosum, and its anti-inflammatory, immunomodulatory and antiangiogenic activities are considered in many other refractory diseases. The aim is to develop derivatives that are not teratogenic but maintain the therapeutic potential. This requires detailed knowledge about the underlying molecular mechanisms. Much progress has been made in deciphering the teratogenic mechanisms in the last decade. Here, we summarize these mechanisms, explain thalidomide resistance of rodents, and discuss possible mechanisms that could explain why the drug primarily targets the developing limb in the embryo. We also summarize the most important therapeutic mechanisms. Finally, we discuss which therapeutic and teratogenic mechanisms do and do not overlap, and if there is a chance for the development of non-teratogenic thalidomide derivatives with therapeutic potential.
Keywords: angiogenesis